Fiscal Consolidation and Recovery in Armenia - Coulibaly, Souleymane (World Bank, Washington, DC, 2012)
Armenia's strong economic growth from 2001-2008, when real gross domestic product (GDP) grew 12.6 percent per year on average, boosted living standards and created the fiscal headroom necessary for the Government to respond to the 2009 financial crisis with a large fiscal stimulus. As a result, the fiscal deficit reached 7.6 percent in 2009 and helped limit the contraction in real GDP to 14 percent. With the economy growing again, the stimulus has to be gradually withdrawn. However, the retrenchment will need to be designed carefully to limit negative impact on growth. Improving the efficiency of all aspects of public finances - tax policy, tax administration, and public expenditures - will be crucial to the planned fiscal adjustment. With the ratio of tax revenues to GDP lower than that of comparator countries with similar levels of income per capita, the brunt of the fiscal consolidation should be borne by an increase in tax revenues (the lower bound estimated to be between 2.3 and 5.8 percent of GDP).